Preservation and Development Strategies of Gorontalo’s Local Culture through Gorontalo Cultural Digital Repository Application - Arip Mulyanto; Mukhlisulfatih Latief; Manda Rohandi; S Supriyadi (Institut Seni Indonesia Denpasar, 2016)
This study aims to implement a strategy of preservation and development of Gorontalo’s local culture through a web based application that can store and display the digitizing results of Gorontalo’s local culture called “Gorontalo cultural digital repository